Bonding Pictures: Affective Ratings Are Specifically Associated to Loneliness But Not to Empathy - Silva, Heraldo D.; Campagnoli, Rafaela R.; Mota, Bruna Eugênia F.; Araújo, Cássia Regina V.; Álvares, Roberta Sônia R.; Mocaiber, Izabela; Rocha-Rego, Vanessa; Volchan, Eliane; Souza, Gabriela G. L. (Frontiers in Psychology, 2017)
Responding to pro-social cues plays an important adaptive role in humans. Our aims were (i) to create a catalogue of bonding and matched-control pictures to compare the emotional reports of valence and arousal with the International Affective Picture System (IAPS) pictures; (ii) to verify sex influence on the valence and arousal of bonding and matched-control pictures; (iii) to investigate if empathy and loneliness traits exert a specific influence on emotional reports for the bonding pictures. To provide a finer tool for social interaction studies, the present work defined two new sets of pictures consisting of “interacting dyads” (Bonding: N=70) and matched controls “non-interacting dyads” (Controls: N=70). The dyads could be either a child and an adult, or two children. Participants (N=283, 182 women) were divided in 10 groups for the experimental sessions. The task was to rate the hedonic valence and emotional arousal of bonding and controls; and of pleasant, neutral, and unpleasant pictures from the IAPS. Effects of social-related traits, empathy and loneliness, on affective ratings were tested. Participants rated bonding pictures as more pleasant and arousing than control ones. Ratings did not differentiate bonding from IAPS pleasant pictures. Control pictures showed lower ratings than pleasant but higher ratings than neutral IAPS pictures. Women rated bonding and control pictures as more positive than men. There was no sex difference for arousal ratings. High empathic participants rated bonding and control pictures higher than low empathic participants. Also, they rated pleasant IAPS pictures more positive and arousing; and unpleasant pictures more negative and arousing than the less empathic ones. Loneliness trait, on the other hand, affected very specifically the ratings of bonding pictures; lonelier participants rated them less pleasant and less arousing than less lonely. Loneliness trait did not modulate ratings of other categories. In conclusion, high empathy seems related to emotional strength in general, while high loneliness seems to weaken the engagement in social interaction cues.